Endoscopic 4-MHz Radiofrequency Treatment of Facet Joint Syndrome Is More Than Just Denervation: One Incision for Three Facets - Woiciechowsky, Christian; Richter, Leonie Mercedes (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims Low back pain is well documented as an extremely common health problem. The most frequently used treatment is radiofrequency denervation for chronic low back pain. However, different clinical studies could only show a limited to no improvement regarding the decrease of pain intensity and duration of the effect. The main reasons for these limited effects seem to be due to the size of the lesion and difficulties in locating the exact placement of the cannula near the medial branch as well as or additional pathologies. Using an endoscope, it is possible to coagulate the facet joints and the medial branch under visual control and consider other pathologies such as extraspinal synovial cysts.Patients In this retrospective study, we included 28 patients with low back pain, with a duration > 6 months and a 50% pain reduction on the numeric analog scale (NAS) after a diagnostic block. All patients received endoscopic facet joint denervation of three facets on the left and right side using only one incision on each side with an exploration of the surrounding tissue. Telephone interviews were conducted with all patients. The outcome was determined with Odom's criteria, percentage reduction NAS, subjective assessment of the patient, and duration of the effect.Results According to Odom's criteria, 68% of the patients showed “acceptable” to “excellent” results and confirmed that denervation helped them manage their daily lives better. The average pain reduction in the responder group was 47% with an average duration of 7.8 months.Conclusion In this retrospective study, we demonstrated the practicability and effectiveness of the endoscopic facet joint denervation procedure in the treatment of chronic low back pain using only one incision for three facets. Further studies should investigate if this procedure is more effective than percutaneous radiofrequency denervation.
Keywords: facet joint syndrome; facet joint denervation; radiofrequency; rhizotomy; spinal endoscopy